Spatial and Temporal Variation in Selection of Genes Associated with Pearl Millet Varietal Quantitative Traits In situ - Mariac, Cédric; Ousseini, Issaka S.; Alio, Abdel-Kader; Jugdé, Hélène; Pham, Jean-Louis; Bezançon, Gilles; Ronfort, Joelle; Descroix, Luc; Vigouroux, Yves (Frontiers in Genetics, 2016)
Ongoing global climate changes imply new challenges for agriculture. Whether plants and crops can adapt to such rapid changes is still a widely debated question. We previously showed adaptation in the form of earlier flowering in pearl millet at the scale of a whole country over three decades. However, this analysis did not deal with variability of year to year selection. To understand and possibly manage plant and crop adaptation, we need more knowledge of how selection acts in situ. Is selection gradual, abrupt, and does it vary in space and over time? In the present study, we tracked the evolution of allele frequency in two genes associated with pearl millet phenotypic variation in situ. We sampled 17 populations of cultivated pearl millet over a period of two years. We tracked changes in allele frequencies in these populations by genotyping more than seven thousand individuals. We demonstrate that several allele frequencies changes are compatible with selection, by correcting allele frequency changes associated with genetic drift. We found marked variation in allele frequencies from year to year, suggesting a variable selection effect in space and over time. We estimated the strength of selection associated with variations in allele frequency. Our results suggest that the polymorphism maintained at the genes we studied is partially explained by the spatial and temporal variability of selection. In response to environmental changes, traditional pearl millet varieties could rapidly adapt thanks to this available functional variability.